Resin composition as well as preparation method and application thereof
By using acrylonitrile-butadiene-styrene resin material and chemically coated hydroxyapatite in mahjong plaque materials, the problems of poor wear resistance and high cost of existing materials are solved, and high impact strength is achieved and a resin composition with good wear resistance, and is non-toxic and environmentally friendly.
Patent Information
- Application Number
- CN202411740838.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
The existing mahjong plaque melamine resin has toxicity and high cost. The wear resistance of ABS materials is poor, making it difficult to have high impact strength and good wear resistance.
The acrylonitrile-butadiene-styrene resin material is used to combine with hydroxyapatite with chemically coated with long carbon chain alkyl groups on the surface. The combination of hydroxyapatite with a specific content and resin material can be improved. Wear resistance and impact resistance.
The resin composition has high impact strength and good wear resistance, and is low in cost and non-toxic and environmentally friendly.
Smart Images

Figure BDA0005162572150000091 
Figure BDA0005162572150000092 
Figure BDA0005162572150000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a resin composition and a preparation method and application thereof. Background Art
[0002] As a widely popular entertainment tool, the selection of materials used to make mahjong has a direct impact on its quality and player experience. Most mahjong tiles on the market are made of melamine resin (melamine formaldehyde resin), which is favored for its high strength, delicate feel and excellent wear resistance. However, the production process of melamine resin may involve the use of formaldehyde, which is toxic and has a high cost. Therefore, seeking less toxic or even non-toxic, low-cost materials to replace melamine resin in making mahjong tiles is a problem of concern in the industry.
[0003] ABS plastic (acrylonitrile-butadiene-styrene copolymer) is widely used in the electronics and electrical industries due to its low cost, high impact strength and good gloss. Studies have found that ABS plastic also shows great application potential in the field of mahjong manufacturing. It can not only reduce production costs, but also has the advantages of easy processing and coloring. However, compared with melamine resin, ABS material has poor wear resistance.
[0004] CN111234442A discloses a wear-resistant ABS composite material and a preparation method thereof, wherein the wear-resistant ABS composite material is composed of ABS, polyvinyl chloride, wear-resistant material, antioxidant and lubricant, and the wear-resistant material is prepared by mixing nano molybdenum disulfide, polytetrafluoroethylene, coupling agent A-172 and mica powder. However, the wear-resistant ABS composite material involves many components, has high cost, and the wear resistance and toughness need to be further improved.
[0005] Therefore, developing a resin material that has both excellent wear resistance and high impact strength and is low in cost, non-toxic and environmentally friendly is an issue that needs to be urgently addressed in the art. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a resin composition and a preparation method and application thereof. The resin composition has both excellent wear resistance and high impact strength, solves the problem that mahjong tiles made of ABS material have poor wear resistance and cannot have both high impact strength and good wear resistance, and has low cost, non-toxic and environmentally friendly.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a resin composition, which includes an acrylonitrile-butadiene-styrene resin material and hydroxyapatite; based on 100 parts by mass of the acrylonitrile-butadiene-styrene resin material, the mass of the hydroxyapatite is 1.5 to 13 parts; the surface of the hydroxyapatite is coated with a long carbon chain alkyl; the long carbon chain alkyl is connected to the hydroxyapatite by a chemical bond.
[0009] In the present invention, long carbon chain alkyl is used to chemically coat hydroxyapatite, which can effectively reduce the polarity of the hydroxyapatite surface; at the same time, the metal ions can effectively coordinate with the cyano group in the acrylonitrile-butadiene-styrene resin material, enhance the interface interaction between the matrix and the matrix, improve the compatibility between the resin materials, and improve the gloss and impact resistance of the resin material while ensuring the wear resistance of the resin material; by compounding hydroxyapatite with a specific content and the acrylonitrile-butadiene-styrene resin material, the obtained resin composition can have both high impact strength and good wear resistance.
[0010] In the present invention, based on 100 parts by mass of the acrylonitrile-butadiene-styrene resin material, the modified hydroxyapatite is 1.5 to 13 parts, for example, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts, 4.8 parts, 5 parts, 5.2 parts, 5.5 parts, 5.8 parts, 6 parts, 6.2 parts, 6.5 parts, 6.8 parts, 7 parts, 7 .2 parts, 7.5 parts, 7.8 parts, 8 parts, 8.2 parts, 8.5 parts, 8.8 parts, 9 parts, 9.2 parts, 9.5 parts, 9.8 parts, 10 parts, 10.2 parts, 10.5 parts, 10.8 parts, 11 parts, 11.2 parts, 11.5 parts, 11.8 parts, 12 parts, 12.2 parts, 12.5 parts, 12.8 parts, 13 parts or a range between any of the above values; preferably 2 to 12.5 parts, more preferably 5 to 11.5 parts.
[0011] In the present invention, if the proportion of the hydroxyapatite is too small, the wear resistance of the resin composition is poor; if the proportion is too large, the impact resistance of the resin composition is poor.
[0012] In the present invention, the long carbon chain alkyl includes C12 to C20 straight chain alkyl, for example, C12 straight chain alkyl, C13 straight chain alkyl, C14 straight chain alkyl, C15 straight chain alkyl, C16 straight chain alkyl, C17 straight chain alkyl, C18 straight chain alkyl, C19 straight chain alkyl, and C20 straight chain alkyl.
[0013] Preferably, the long carbon chain alkyl group is derived from a long carbon chain carboxylate.
[0014] In the present invention, the long-chain carboxylate includes C12-C20 carboxylates, illustratively including but not limited to stearates; the long-chain carboxylate includes at least one of zinc salt, calcium salt or magnesium salt; illustratively, includes at least one of magnesium stearate, zinc stearate or calcium stearate.
[0015] Preferably, based on 100 parts of hydroxyapatite, the addition amount of the long carbon chain carboxylate is 50 to 150 parts, for example, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 96 parts, 98 parts, 100 parts, 10 2 parts, 105 parts, 108 parts, 110 parts, 112 parts, 115 parts, 118 parts, 120 parts, 122 parts, 125 parts, 128 parts, 130 parts, 132 parts, 135 parts, 138 parts, 140 parts, 142 parts, 145 parts, 148 parts, 150 parts or the range between any of the above values; more preferably, the addition amount of the long chain carboxylate is 85 to 115 parts, and particularly preferably, the addition amount of the long chain carboxylate is 90 to 110 parts.
[0016] Preferably, the long carbon chain carboxylate is linked to hydroxyapatite via an ionic bond.
[0017] Preferably, the hydroxyapatite further comprises metal ions B, and the metal ions B comprise zinc ions and / or magnesium ions.
[0018] In the present invention, the metal ion B is derived from the aforementioned long carbon chain carboxylate; the long carbon chain carboxylate reacts with hydroxyapatite to undergo ion exchange, thereby introducing the metal ion B and, at the same time, grafting and coating the long carbon chain alkyl on the surface of hydroxyapatite.
[0019] In the present invention, the mass percentage of metal ion B in the hydroxyapatite is 15-30%, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or the range between any of the above values, and more preferably the mass percentage of metal ion B is 20-27%.
[0020] In the present invention, the mass percentage of metal ions B in hydroxyapatite can be measured by an element analyzer (such as using an inductively coupled plasma mass spectrometer ICP-MS for testing).
[0021] Preferably, the D90 particle size of the hydroxyapatite is 150 to 5000 nm, for example, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, 1050 nm, 1100 nm, 1150 nm, 1200 nm, 1300 nm. , 1400nm, 1500nm, 1600nm, 1800nm, 2000nm, 2200nm, 2400nm, 2600nm, 2800nm, 3000nm, 3200nm, 3500nm, 3800nm, 4000nm, 4200nm, 4500nm, 4800nm, 5000nm or ranges between any of the above values; more preferably, the D90 particle size is 500-1000nm, and particularly preferably, the D90 particle size is 650-950nm.
[0022] In the present invention, D90 particle size refers to the particle size value corresponding to when the cumulative distribution percentage from small to large reaches 90% in the particle size distribution.
[0023] In the present invention, the hydroxyapatite can be prepared by conventional methods, as long as hydroxyapatite of a corresponding structure is obtained; illustratively, the preparation method includes:
[0024] According to the formula, hydroxyapatite, long carbon chain carboxylate and solvent are mixed, heated and refluxed to obtain the hydroxy limestone.
[0025] In the present invention, the reflux temperature is 80-120°C, and the reflux time is 2-5h; after the reflux is completed, a post-treatment step is also included; the post-treatment includes filtration, washing and vacuum drying; the vacuum drying temperature is 50-70°C.
[0026] Preferably, the acrylonitrile-butadiene-styrene resin material includes acrylonitrile-butadiene-styrene resin or a mixture of acrylonitrile-styrene copolymer and butadiene-acrylonitrile-styrene graft copolymer.
[0027] In the present invention, according to ASTM D1238-2010 standard, at 220° C. and 10 kg, the melt index of the acrylonitrile-butadiene-styrene resin material is 20 to 40 g / 10 min, for example, it can be 20 g / 10 min, 21 g / 10 min, 22 g / 10 min, 23 g / 10 min, 24 g / 10 min, 25 g / 10 min, 26 g / 10 min, 27 g / 10 min, 28 g / 10 min, 29 g / 10 min, 30 g / 10 min, 31 g / 10 min, 32 g / 10 min, 33 g / 10 min, 34 g / 10 min, 35 g / 10 min, 36 g / 10 min, 37 g / 10 min, 38 g / 10 min, 39 g / 10 min, 40 g / 10 min or the range between any of the above values.
[0028] Preferably, based on 100 parts by mass of the acrylonitrile-butadiene-styrene resin material, the resin composition further includes 0.5 to 6.5 parts of an auxiliary agent, for example, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5 or a range between any of the above values.
[0029] Preferably, the auxiliary agent comprises an antioxidant and / or a lubricant.
[0030] Preferably, the auxiliary agent includes 0.5 to 5 parts of lubricant (for example, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any range between the above values) and 0.2 to 1 parts of antioxidant (for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part or any range between the above values) by weight.
[0031] In the present invention, the antioxidant includes but is not limited to tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester (antioxidant 1010), β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester (antioxidant 1076), N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine (antioxidant 1098), etc.; the phosphite antioxidant includes but is not limited to tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168), bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite (antioxidant 626), etc.
[0032] In the present invention, the lubricant includes but is not limited to vinyl bisstearamide, erucic acid amide and the like.
[0033] In the present invention, the resin composition may also be added with other additives as needed, illustratively including but not limited to colorants, antistatic agents (such as ethoxy lauric acid amine, dilauryl phosphate, glycerol monostearate, etc.), coupling agents (such as silane coupling agents, titanate coupling agents, etc.), compatibilizers (such as maleic anhydride grafted acrylonitrile-butadiene-styrene polymers, etc.), flame retardants (such as aluminum hydroxide, magnesium hydroxide, ammonium polyphosphate, melamine derivatives, etc.), etc.
[0034] Preferably, according to the GB / T1843-2008 test standard, the notched cantilever beam impact strength of the resin composition is ≥13 kJ / m 2 , preferably ≥15kJ / m 2 , more preferably ≥17 kJ / m 2 .
[0035] Preferably, according to standard JIS K7218-1986, after being worn 2000 times at a single arm load of 500 g and a rotation speed of 60 r / min, the weight loss of the resin composition is ≤65 mg, more preferably ≤63 mg, more preferably ≤42 mg, and particularly preferably ≤32 mg.
[0036] In a second aspect, the present invention provides a method for preparing the resin composition according to the first aspect, the preparation method comprising the following steps:
[0037] The acrylonitrile-butadiene-styrene resin material and hydroxyapatite are mixed and extruded to obtain the resin composition; the surface of the hydroxyapatite is coated with a long carbon chain alkyl; the long carbon chain alkyl is connected to the hydroxyapatite through a chemical bond.
[0038] Preferably, the mixing time is 1 to 10 minutes.
[0039] Preferably, the extrusion temperature is 150-230°C.
[0040] In the present invention, the mixing is carried out in a mixer; the rotating speed of the mixing is 50-200 rpm; the extrusion is carried out in a twin-screw extruder, and the temperature ranges of the twin-screw extruder are as follows: zone 1 150-180°C; zone 2 180-200°C; zone 3 180-200°C; zone 4 190-210°C; zone 5 200-220°C; zone 6 200-220°C; zone 7 200-220°C; zone 8 210-230°C; zone 9 210-230°C; zone 10 210-230°C; zone 11 210-230°C; the rotating speed of the twin-screw extruder is 300-600 rpm, and the aspect ratio is 40-44:1.
[0041] In a third aspect, the present invention provides a mahjong tile, wherein the material of the mahjong tile comprises the resin composition according to the first aspect.
[0042] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The resin composition provided by the present invention is added with hydroxyapatite coated with a long carbon chain alkyl on the surface, and the hydroxyapatite and the acrylonitrile-butadiene-styrene resin material are compounded in a controlled manner at a specific content, so that the resin composition can have both high impact strength and good wear resistance, and has low toxicity and low cost. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0046] Unless otherwise specified, the materials used in the present invention can be purchased from the market or prepared by conventional methods; the materials used in the present invention are as follows:
[0047] ABS 730: Liaoning Jinfa, according to ASTM D1238-2010 standard, the melt index at 220℃, 10kg is 24g / 10min.
[0048] Hydroxyapatite (HAP): Hydroxyapatite of corresponding particle size can be directly purchased from the market, or purchased large-particle hydroxyapatite can be ground to obtain hydroxyapatite of corresponding particle size; the D90 particle size of the hydroxyapatite is obtained by testing with a particle size analyzer.
[0049] HAP-1: D90 particle size is 650 nm and was purchased from Nanjing Junzhuo Chemical Co., Ltd.
[0050] HAP-2: D90 particle size is 900 nm and was purchased from Chengdu Zhongding Kairui Co., Ltd.
[0051] HAP-3: D90 particle size is 200 nm and was purchased from Wuhan Shuer Biotechnology Co., Ltd.
[0052] HAP-4: D90 particle size is 2 μm, purchased from Jicang Nano, 96-2u.
[0053] Nylon: PA66, American DuPont 101F.
[0054] Antioxidant: A composite antioxidant consisting of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol and bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite in a mass ratio of 1:1, which is commercially available.
[0055] Lubricant: Erucic acid amide, commercially available.
[0056] Preparation Examples 1 to 10, Comparative Preparation Examples 1 to 4
[0057] Preparation Examples 1 to 10 and Comparative Preparation Examples 1 to 4 respectively provide a hydroxyapatite, wherein the raw materials for preparing the hydroxyapatite include hydroxyapatite and a long-chain carboxylate; based on the mass of hydroxyapatite as 100 parts by weight, the weight fractions and types of the long-chain carboxylates are shown in Tables 1 and 2; wherein, “ / ” indicates that the component is not included in the formula.
[0058] Unless otherwise specified, the preparation method of hydroxyapatite comprises:
[0059] According to the formula, hydroxyapatite and long-chain carboxylate are placed in a reaction kettle, 1L of distilled water is added, the reaction temperature is raised to 100°C, refluxed for 4 hours, and then filtered, washed with deionized water, and vacuum dried at 60°C to obtain the hydroxyapatite. The difference between different hydroxyapatites lies only in the type and amount of long-chain carboxylate.
[0060] Among them, the preparation method of hydroxyapatite provided in Preparation Example 2 includes: placing hydroxyapatite and long-chain carboxylate in a reaction kettle, adding 1L of distilled water, raising the reaction temperature to 120°C, reflux for 2h, and then filtering, washing with deionized water, and vacuum drying at 70°C to obtain the hydroxyapatite.
[0061] The preparation method of hydroxyapatite provided in comparative preparation example 1 includes: mixing hydroxyapatite with PA66.
[0062] In the present invention, the content of metal ions B (zinc ions or magnesium ions) in the hydroxyapatite can be tested by inductively coupled plasma mass spectrometry (ICP-MS).
[0063] Table 1
[0064]
[0065]
[0066] Table 2
[0067]
[0068] Examples 1 to 14, Comparative Examples 1 to 7
[0069] Examples 1 to 14 and Comparative Examples 1 to 7 provide a resin composition, respectively. The formulas of the resin compositions are shown in Tables 3 to 5 in parts by weight; wherein “ / ” indicates that the component is not included in the formula; and the preparation method of the resin composition comprises:
[0070] ABS resin, hydroxyapatite and optional antioxidant and lubricant are mixed in a mixer at a rotation speed of 100 rpm for 4 minutes to obtain a mixture A; then the mixture A is put into a twin-screw extruder with a length-to-diameter ratio of 40:1, a temperature range of 160°C, 190°C, 190°C, 200°C, 210°C, 210°C, 220°C, 220°C, 220°C, and a rotation speed of 450 rpm, and the resin composition is obtained by melting, extruding and granulating.
[0071] Table 3
[0072]
[0073] Table 4
[0074]
[0075]
[0076] Table 5
[0077]
[0078]
[0079] Comparative Example 7
[0080] This comparative example provides a resin composition, which is different from Example 2 only in that the hydroxyapatite and zinc stearate are not connected by chemical bonds but are physically mixed. In the preparation method of the resin composition, the hydroxyapatite with zinc stearate grafted on the surface is replaced by HAP-1 and zinc stearate of equal mass in a mass ratio of 1:1, and the other steps are the same as Example 2.
[0081] Performance Testing
[0082] (1) Izod notched impact strength: The notched Izod impact strength of the resin compositions provided in Examples 1 to 14 and Comparative Examples 1 to 7 was tested in accordance with GB / T 1843-2008, “Determination of Izod Impact Strength of Plastics”.
[0083] (2) Wear resistance: According to standard JIS K7218-1986, the resin compositions provided in Examples 1 to 14 and Comparative Examples 1 to 7 were injection molded to obtain square plates of 3 mm × 100 mm × 100 mm. The mass change of the square plates before and after wear was tested using an abrasion tester. The test parameters of the abrasion tester were as follows: single arm load: 500 g; grinding wheel model: H-18; sample rotation speed: 60 r / min; number of rotational frictions: 2000 rotations. The smaller the mass change before and after wear, the better the wear resistance.
[0084] Pure ABS resin was used as the control group.
[0085] The specific test results are shown in Table 6.
[0086] Table 6
[0087]
[0088]
[0089] As shown in Table 6, the resin composition provided by the present invention uses a long carbon chain alkyl to chemically coat hydroxyapatite, and controls the hydroxyapatite and the acrylonitrile-butadiene-styrene resin material to be compounded in a specific content, so that the resin composition can have both high impact strength and good wear resistance. Compared with pure ABS resin, the wear resistance is significantly improved, and at the same time, the material can still have good impact toughness; the cantilever beam notched impact strength of the resin composition is ≥13kJ / m 2 The mass change before and after wear is ≤65mg.
[0090] It can be seen from the comparative examples that when unmodified hydroxyapatite is used or hydroxyapatite is not chemically coated with a long carbon chain alkyl, or the modified hydroxyapatite is replaced with modified mica powder, the impact toughness or wear resistance of the resin composition is significantly deteriorated.
[0091] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A resin composition, characterized in that The resin composition comprises acrylonitrile-butadiene-styrene resin material and hydroxyapatite; Based on 100 parts by weight of the acrylonitrile-butadiene-styrene resin material, the weight of the hydroxyapatite is 1.5 to 13 parts; The surface of the hydroxyapatite is coated with a long carbon chain alkyl; The long carbon chain alkyl is connected to hydroxyapatite via a chemical bond.
2. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the acrylonitrile-butadiene-styrene resin material, the weight of the hydroxyapatite is 2 to 12.5 parts, and preferably the weight of the hydroxyapatite is 5 to 11.5 parts.
3. The resin composition according to claim 1, characterized in that The long carbon chain alkyl includes C12 to C20 straight chain alkyl; Preferably, the long carbon chain alkyl group is derived from a long carbon chain carboxylate; Preferably, based on 100 parts of hydroxyapatite, the addition amount of the long carbon chain carboxylate is 50 to 150 parts, and more preferably the addition amount of the long carbon chain carboxylate is 85 to 115 parts; Preferably, the long carbon chain carboxylate is linked to hydroxyapatite via an ionic bond.
4. The resin composition according to any one of claims 1 to 3, characterized in that The hydroxyapatite further comprises metal ions B, wherein the metal ions B comprise zinc ions and / or magnesium ions; Preferably, the mass percentage of metal ion B in the hydroxyapatite is 15-30%, more preferably 20-27%; Preferably, the D90 particle size of the hydroxyapatite is 150 to 5000 nm, more preferably the D90 particle size is 500 to 1000 nm.
5. The resin composition according to any one of claims 1 to 4, characterized in that The acrylonitrile-butadiene-styrene resin material includes acrylonitrile-butadiene-styrene resin or a mixture of acrylonitrile-styrene copolymer and butadiene-acrylonitrile-styrene graft copolymer.
6. The resin composition according to any one of claims 1 to 5, characterized in that Based on 100 parts by weight of the acrylonitrile-butadiene-styrene resin material, the resin composition further comprises 0.5 to 6.5 parts of an auxiliary agent; Preferably, the auxiliary agent includes an antioxidant and / or a lubricant; Preferably, the auxiliary agent includes 0.5 to 5 parts of lubricant and 0.2 to 1 parts of antioxidant in parts by weight.
7. The resin composition according to any one of claims 1 to 6, characterized in that According to the GB / T1843-2008 test standard, the notched cantilever beam impact strength of the resin composition is ≥13 kJ / m 2 ; Preferably, after being worn 2000 times under the conditions of a single-arm load of 500 g and a rotation speed of 60 r / min, the weight loss of the resin composition is ≤65 mg.
8. A method for preparing a resin composition according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The acrylonitrile-butadiene-styrene resin material and hydroxyapatite are mixed and extruded to obtain the resin composition; the surface of the hydroxyapatite is coated with a long carbon chain alkyl; the long carbon chain alkyl is connected to the hydroxyapatite through a chemical bond.
9. The preparation method according to claim 8, characterized in that: The mixing time is 1 to 10 minutes; Preferably, the extrusion temperature is 150-230°C.
10. A mahjong tile, characterized in that: The material of the mahjong tiles comprises the resin composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Wear-resistant ABS composite material and preparation method thereof
CN111234442A